Comparison of Endovascular Embolization Plus Simultaneous Microsurgical Resection vs. Primary Microsurgical Resection for High-Grade Brain Arteriovenous Malformations - Wang, Mingze; Lin, Fa; Qiu, Hancheng; Cao, Yong; Wang, Shuo; Zhao, Jizong (Frontiers in Neurology, 2021)
Aim Surgical treatments of brain arteriovenous malformations (AVMs) in Spetzler-Martin Grade (SMG) IV and V remained a challenge to achieve both optimal neurological outcomes and complete obliteration. The author reported a series of patients with the AVMs in SMG IV and V who underwent a surgical paradigm of endovascular embolization and simultaneous microsurgical resection based on the one-staged hybrid operation. Methods Participants in the multicenter prospective clinical trial (NCT 03774017) between January 2016 and December 2019 were enrolled. Patients who received endovascular embolization plus microsurgical resection (EE+MRS) and those who received intraoperative digital subtraction angiography plus microsurgical resection (iDSA+MRS) were divided into two groups. Information on clinical features, operative details, and clinical outcomes were extracted from the database. Deterioration of neurological deficits (DNDs) was defined as the primary outcome, which represented neurological outcomes. The time of microsurgical operation and blood loss was defined as the secondary outcomes representing microsurgical risks and difficulties. Outcomes and technical details were compared between groups. Results Thirty-eight cases (male: female = 23:15) were enrolled with 24 cases in the EE+MRS group and 14 in the iDSA+MRS group. Five cases (13.2%) were in SMG V, and 33 cases (86.8%) were in SMG IV. Fourteen cases (36.8%) underwent the paradigm of microsurgical resection plus intraoperative DSA. Twenty-four cases (63.2%n=24) underwent the paradigm of endovascular embolization plus simultaneous microsurgical resection. Degradations of SMG were achieved in 15 cases. Two cases got the residual nidus detected via intraoperative DSA and resected. Deterioration of neurological deficits occurred in 23.7% of cases (n=9) when discharge, and in 13.5%, 13.5%, 8.1% of cases at the follow-ups of 3, 6, and 12 months, respectively, without significant difference between groups (P>0.05). Intracranial hemorrhagic complications were reported in 3 cases (7.9%) of the EE+MRS group only. The embolization did not significantly affect the surgical time and intraoperative blood loss. The subtotal embolization or the degradation of size by 2 points resulted in no DNDs. Conclusions The paradigms based on the one-staged hybrid operation were practical and effective in treating high-grade AVMs. Appropriate intraoperative embolization could help decrease operative risks and difficulties and improve neurological outcomes.